Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Kepuasan Nasabah Peminjam 10 Juta Tahun 2021 - Restu Widiandari; Ustadus Sholihin; Edi Murdiyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Influence of Service Quality of the Activity Management Unit which consists of variables physical evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance) and attention (empathy) are very important for find out how much influence it has on Unit customer satisfaction Activities Manager at the Institutional Inter-Village Cooperation Agency in Banyakan Kediri District. By knowing this relationship, the parties The Activity Management Unit can estimate how the community will respond regarding the services that have been provided so that plans can be made and improve the services that will be provided in the future. The sampling technique in this research used purposive sample and in accordance with quantitative research. Meanwhile, the samples taken is a customer of the Banyakan District Activity Management Unit. The data obtained through Questionnaire I questionnaires, observations and interviews. From the results analysis that has been carried out, the research results show that quality service has a significant effect on customer satisfaction. That matter It is known from the results of the correlation analysis as follows: r value = 0.962 or 96.2% which means the magnitude of the correlation is close to 100%.